2019
DOI: 10.1093/cid/ciz1075
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cholera in Bangladesh: Findings From Nationwide Hospital-based Surveillance, 2014–2018

Abstract: Background Despite advances in prevention, detection, and treatment, cholera remains a major public health problem in Bangladesh and little is known about cholera outside of limited historical sentinel surveillance sites. In Bangladesh, a comprehensive national cholera control plan is essential, although national data are needed to better understand the magnitude and geographic distribution of cholera. Methods We conducted sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 22 publications
5
51
0
Order By: Relevance
“…Based on limited data from clinical sentinel surveillance, cholera case reports in 2015 were consistent with historic trends. 24 However, our estimates might not generalise to all future years because of natural variation in infection incidence driven by both intrinsic and extrinsic factors. Among the individual-level, household-level, and community-level covariates considered by us, only age was a strong predictor of risk for seropositivity.…”
Section: Table: Estimated Associations Between Individual-level Household-level and Community-level Factors And Seropositivity From Spatimentioning
confidence: 97%
“…Based on limited data from clinical sentinel surveillance, cholera case reports in 2015 were consistent with historic trends. 24 However, our estimates might not generalise to all future years because of natural variation in infection incidence driven by both intrinsic and extrinsic factors. Among the individual-level, household-level, and community-level covariates considered by us, only age was a strong predictor of risk for seropositivity.…”
Section: Table: Estimated Associations Between Individual-level Household-level and Community-level Factors And Seropositivity From Spatimentioning
confidence: 97%
“…In this study, we coupled an existing nationwide enteric disease surveillance study across Bangladesh with a WGS approach to investigate the genomic epidemiology of S. enterica serotype Paratyphi B complex. Our surveillance showed that, in Bangladesh, the prevalence of S. Paratyphi B isolates is low (0.36%) compared to other enteric pathogens in this surveillance study [14]. Moreover, where previous studies have only reported serotyping results of S. Paratyphi B strains [53], this is the first study in Bangladesh to distinguish between S. Java and S. Paratyphi B sensu stricto biotypes, using WGS to confirm that S. Java is the variant responsible for the diarrhoeal disease in Bangladesh.…”
Section: Discussionmentioning
confidence: 52%
“…This study utilized samples collected from an established nationwide enteric disease surveillance system being carried out in 10 hospitals across 8 divisions of Bangladesh in a collaboration between the Institute of Epidemiology, Disease Control and Research (IEDCR) and icddr,b (, ). The surveillance sites were selected based on reports of acute watery diarrhoea according to the national District Health Information Software v2 Database from Directorate General of Health Services (DGHS) [14, 15]. It is a large, longitudinal, multi-pathogen surveillance study that included diarrhoeal patients infected with a variety of enteric pathogens: Vibrio cholerae , ETEC, Shigella , and typhoidal and non-typhoidal Salmonella .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bangladesh has among the highest national rates of Vibrio cholerae infection in the world [1]; a nationally-representative serosurvey estimated that roughly 17% (95% CI: 11-24%) of the 165 million people living in Bangladesh experienced infection in 2015 [2]. In 2014, the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b) and the Institute of Epidemiology Disease Control And Research (IEDCR) established a nationwide sentinel surveillance system with the goal of monitoring the seasonality and geographic trends in acute cases and identifying geographic areas with a high burden of laboratory-confirmed clinical cholera [3]. The participating 22 sentinel hospital sites and the icddr,b Dhaka hospital are the only healthcare facilities that regularly perform laboratory confirmation of V. cholerae in the country [3].…”
Section: Introductionmentioning
confidence: 99%